2019
DOI: 10.1007/978-3-030-25650-0_9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Herbal Products in the Prevention, Regeneration and Delay of Skin Aging

Abstract: Advances in Experimental Medicine and Biology presents multidisciplinary and dynamic findings in the broad fields of experimental medicine and biology. The wide variety in topics it presents offers readers multiple perspectives on a variety of disciplines including neuroscience, microbiology, immunology, biochemistry, biomedical engineering and cancer research. Advances in Experimental Medicine and Biology has been publishing exceptional works in the field for over 30 years and is indexed in Medline, Scopus, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…15,16 Currently, combination therapy is an attractive strategy involving the impaired intrinsic antioxidant defense system complemented by exogenous factors, such as polyphenols and vitamins present in natural products. [5][6][7][8][17][18][19] In the present study, two novel phenolic glycosides, namely citrulluside UV-B changes the structure of trans-urocanic acid and tryptophan to cis-urocanic acid and 6-formylindolo-3,2-carbazole (FICZ), respectively, which alters their original biological activities. 27 FICZ is well established as an endogenous aryl hydrocarbon receptor (AhR) ligand.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…15,16 Currently, combination therapy is an attractive strategy involving the impaired intrinsic antioxidant defense system complemented by exogenous factors, such as polyphenols and vitamins present in natural products. [5][6][7][8][17][18][19] In the present study, two novel phenolic glycosides, namely citrulluside UV-B changes the structure of trans-urocanic acid and tryptophan to cis-urocanic acid and 6-formylindolo-3,2-carbazole (FICZ), respectively, which alters their original biological activities. 27 FICZ is well established as an endogenous aryl hydrocarbon receptor (AhR) ligand.…”
Section: Discussionmentioning
confidence: 84%
“…As a defense mechanism against photoaging‐induced skin disorders, the skin is endogenously equipped with antioxidants and antioxidant enzymes; however, owing to aging and the resultant skin damage, these defenses are unable to process the ROS generated by UV irradiation 15,16 . Currently, combination therapy is an attractive strategy involving the impaired intrinsic antioxidant defense system complemented by exogenous factors, such as polyphenols and vitamins present in natural products 5‐8,17‐19 . In the present study, two novel phenolic glycosides, namely citrulluside H and citrulluside T, obtained from young watermelon fruit, were found to suppress UV‐B – induced MMP expression in NHDFs via downregulation of the MAPK/AP‐1 and NF‐κB signaling pathways activated by ROS (Figure 6).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In previous research, we have shown that the ethanol extract of Curcuma heyneana rhizome has an antioxidant and antiaging activity that protects the skin from the damaging effects of excessive UV exposure [7][8][9]. This study used a histomorphometric method of rats exposed to UV light [10].…”
Section: Paul C Guest 1 Introductionmentioning
confidence: 99%